1979
DOI: 10.1111/j.1399-0004.1979.tb00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Features of trisomy 18 and 18p‐syndromes in an infant with 46, XY, i(18q)

Abstract: An isochromosome for the long arm of chromosome number 18 ‐ 46, XY, i(18q) ‐ was found in an infant who had features of both trisomy 18 and 18p– syndromes. Findings compatible with trisomy 18 included postmature delivery, prominent occiput, severe congenital heart disease, overlapping fingers, and rocker‐bottom feet. Those of 18p– syndrome, which frequently resembles Turner syndrome, were downward obliquity to the palpebral fissures, short, webbed neck, low posterior hairline, and widely‐spaced nipples. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
2

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 4 publications
1
14
0
2
Order By: Relevance
“…There are, however, only few clinical syndromes due to autosomal isochromosome as are e.g. tetrasomy 18p (for review see Fryns et al 1985) or, much more rarely, trisomy 18 syndrome due to isochromosome 18q formation (Miiller et al 1972, Surana et al 1973, Rodiere et al 1977, Bass et al 1979, Fioretti et al 1982, Froster-Iskenius et al 1984. Finally, Larson et al (1978) reported double isochromosome formation (i(18p) and i(18q)) in the same patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, only few clinical syndromes due to autosomal isochromosome as are e.g. tetrasomy 18p (for review see Fryns et al 1985) or, much more rarely, trisomy 18 syndrome due to isochromosome 18q formation (Miiller et al 1972, Surana et al 1973, Rodiere et al 1977, Bass et al 1979, Fioretti et al 1982, Froster-Iskenius et al 1984. Finally, Larson et al (1978) reported double isochromosome formation (i(18p) and i(18q)) in the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…He presented, in fact, a typical trisomy 18 phenotype confirming that only trisomy 18q, and particularly trisomy of the sole 18qll band, is required for full expression of this phenotype (Fryns & Van den Berghe 1978, Fryns et al 1979). On the other hand, this boy presented with some Turner-like features, i.e., short neck with redundant skin, low posterior hairline and widely spaced nipples, which are believed to be characteristic of monosomy 18p (de Grouchy 1969, Bass et al 1979, Wulfsberg et al 1984.…”
Section: Discussionmentioning
confidence: 99%
“…The typical phenotype of i(18q) is very comparable to complete trisomy 18 and includes severe growth retardation, occipital prominence, low set ears, downward-slanting palpebral fissures, overlapping flexed fingers, rocker-bottom feet, congenital heart defects, and skeletal abnormalities. The monosomy 18p (18p-) often results in psychomotor retardation, short webbed neck, low posterior hairline, hypospadias, male genital anomalies and holoprosencephaly 67. The present fetus who had 18p11.21→qter duplication and 18p11.21→pter deletion demonstrated typical features of trisomy 18, including ventricular septal defect, limbs malformations and skeletal abnormalities.…”
Section: Discussionmentioning
confidence: 65%
“…By using the methods described, however, we cannot absolutely exclude the possibility of finding such a mosaicism in the parents. Bass et al (1979) and Wulfsberg et al (1984) found normal karyotypes in the parents of index cases with i(l8q). Because of the hypothetical possibility of a mosaicism it would be necessary to investigate parental cells of both endo-and ectodermal origin; the parents did not cooperate with us in these studies.…”
Section: Discurnionmentioning
confidence: 95%
“…Partial tisomy (18q) and simultaneous monosomy (1 8p) due to an isochromosome (1 8q) are very rare cytogenetic conditions. Since the first report on an i( 18q) syndrome was presented (Surana et al 1973), only four additional cases of this cytogenetic abnormality have been described (Bass et al 1979, Wulfsberg et al 1984, Froster-Iskenius et al 1984, Rodifire et al 1977. Surprisingly, autopsy findings have only recently been published (Froster-Iskenius et al 1984).…”
mentioning
confidence: 99%